2005
DOI: 10.1007/s00704-004-0111-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of coherent structures in urban turbulence

Abstract: SummaryThe continuous wavelet transform provides a suitable tool to visualize the vertical structure of turbulence and to detect coherent structures in turbulent time series. This is demonstrated with a simple example of an artificially ramp structured time series. In this study turbulence data, i. , sampled with 20.83 Hz and measured simultaneously at three levels (z=h ¼ 1.5, 2.1 and 3.2, with z as the sensor height and h the height of the roughness elements) over an urban canopy in the inner city of Basel, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 24 publications
1
43
0
1
Order By: Relevance
“…Multiple methods are available for wavelet detection of coherent structures (Barthlott et al, 2007;Collineau and Brunet, 1993a;Feigenwinter and Vogt, 2005;Lu and Fitzjarrald, 1994;Thomas and Foken, 2005). Here we employ the method of Barthlott et al (2007), which uses temperature fluctuations to detect ramp structures under stable and unstable conditions.…”
Section: Wavelet Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple methods are available for wavelet detection of coherent structures (Barthlott et al, 2007;Collineau and Brunet, 1993a;Feigenwinter and Vogt, 2005;Lu and Fitzjarrald, 1994;Thomas and Foken, 2005). Here we employ the method of Barthlott et al (2007), which uses temperature fluctuations to detect ramp structures under stable and unstable conditions.…”
Section: Wavelet Analysismentioning
confidence: 99%
“…We select this method because the use of temperature ramps provides a physical basis and easy visualization for the selection of coherent structure events. We apply wavelet analysis to the 10 Hz sonic anemometer temperature records for each 30-min period and use a "Mexican Hat" wavelet, which has been shown to effectively detect coherent structures (e.g., Collineau and Brunet, 1993a;Feigenwinter and Vogt, 2005). For each 30-min time period throughout the field campaign (1152 total periods after pre-processing and filtering), we detect coherent structures according to the following techniques defined in Barthlott et al (2007).…”
Section: Wavelet Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…the review by Britter and Hanna, 2003), but little is currently known about the unsteady flow dynamics. It is now believed that unsteady effects due to organized or coherent structures in urban turbulence must be at least as important, in an order of magnitude sense, as the mean flow (Oikawa and Meng, 1995;Feigenwinter and Vogt, 2005). Yet we still do not have a conceptual model of the unsteady flow, let alone a detailed quantitative understanding that might lend itself to future parameterizations.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we have demonstrated that both kurtosis and phase coherence index techniques are capable of characterizing the degree of departure from Gaussianity, due to phase coherence, of atmospheric intermittent turbulence. The nonlinear techniques discussed in this paper can be applied to investigate the role played by coherent structures in experimental (Gao et al, 1989;Barthlott et al, 2007), theoretical (Raupach, 1996;Harman and Finnigan, 2007), and large-eddy simulation (Su et al, 1998;Qiu et al, 2008) studies of atmospheric turbulence in forest canopy, as well as in orchard canopy (Wang et al, 1992;Stoughton et al, 2002), rice canopy (Gao et al, 2003), corn canopy (Yue et al, 2007;Zhu et al, 2007), cotton and grape canopies (Mitic et al, 1999), coral canopy (Reidenbach et al, 2007), and urban canopy (Feigenwinter and Vogt, 2005;Salmond et al, 2005).…”
Section: Discussionmentioning
confidence: 99%